Transcobalamin C776G Genotype Modifies the Association between Vitamin B12 and Homocysteine in Older Hispanics - Garrod, Marjorie G. (2010)
BACKGROUND: A common polymorphism, C776G, in the plasma B12 transport protein transcobalamin (TC), encodes for either proline or arginine at codon 259. This polymorphism may affect the affinity of TC for B12 and subsequent delivery of B12 to tissues. METHODS: TC genotype and its associations with indicators of B12 status, including total B12, holotranscobalamin (holoTC), methylmalonic acid, and homocysteine, were evaluated in a cohort of elderly Latinos (N=554, age 60–93y) from the Sacramento Area Latino Study on Aging (SALSA). RESULTS: The distribution of TC genotypes was 41.3% homozygous reference (776CC) and 11.6% homozygous variant (776GG). No differences between the homozygous genotypes were observed in total B12, holoTC, methylmalonic acid, or homocysteine. The holoTC/total B12 ratio was lower in the 776GG group compared with the 776CC group (p=0.04). Significant interactions of TC genotype with total B12 (p=0.04) and with holoTC (p≤0.03) were observed such that mean homocysteine concentrations and the odds ratios for hyperhomocysteinemia (>13 µmol/L) were higher in the 776CC subjects compared with all carriers of the G allele (776CG and 776GG combined) when total B12 (<156 pmol/L) or holoTC (<35 pmol/L) were low. CONCLUSIONS: This population of older Latinos has a lower prevalence of the TC 776GG variant than reported for Caucasian populations. The association between vitamin B12 and homocysteine concentrations is modified by TC 776 genotype. It remains to be determined if the TC C776G polymorphism has a significant effect on the hematological and neurological manifestations of B12 deficiency or on vascular and other morbidities associated with hyperhomocysteinemia.